METODE KAPLAN MEIER UNTUK ANALISIS KETAHANAN HIDUP PENDERITA KANKER PAYUDARA DI RSUD KOTA MAKASSAR - Mahrani Mahrani; Muh.Nadjib Bustan; Suwardi Annas (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2021)
this research, using survival analysis with the Kaplan Meier method. The purpose of this research is to know the life resistance of breast cancer survivors in the Regional General Hospital of Makassar city based on the age group of patients, cancer stage group of patients, and measures chemotherapy group of patients. The results of this research show that (i) the survival rate of breast cancer patients (with a sample size of 74 patients over a period of three years) is more than 354 days with a probability of 0.285 or 28.5%. (ii) When viewed from an early age infected the survival rate for 45 years of age is 1 or 100 for 45 years of an age exceeding 354 days with a probability of 0.229 or 22.9%. The probability of survival for breast cancer patients based on stage level variables, namely stage II of 1 or 100%, survival of stage III breast cancer patients exceeding 21 days with a probability of 0.929 or 92.9%, and survival of stage IV breast cancer patients exceeding 354 days with a probability of 0. The survival of patients following chemotherapy exceeded 354 days with a probability of 0.292 and the survival of patients who did not follow chemotherapy exceeded 17 days with a probability of 0.727